Answer:
X=8
Step-by-step explanation:
If you would like to simplify (3 * x + 5) + (2 * x - 9) - (4 * x + 3), you can do this using the following steps:
(3 * x + 5) + (2 * x - 9) - (4 * x + 3) = 3 * x + 2 * x - 4 * x + 5 - 9 - 3 = 1 * x - 7 = x - 7
The correct result would be x - 7.
Answer:
![\pm11,\pm1,\pm\frac{11}{5},\pm\frac{1}{5}](https://tex.z-dn.net/?f=%5Cpm11%2C%5Cpm1%2C%5Cpm%5Cfrac%7B11%7D%7B5%7D%2C%5Cpm%5Cfrac%7B1%7D%7B5%7D)
Step-by-step explanation:
The given polynomial function is
![f(x)=5x^3-7x+11](https://tex.z-dn.net/?f=f%28x%29%3D5x%5E3-7x%2B11)
According to the Rational Roots Theorem, the ratio of all factors of the constant term expressed over the factors of the leading coefficient.
The potential rational roots are
![\pm\frac{11}{1}=\pm11](https://tex.z-dn.net/?f=%5Cpm%5Cfrac%7B11%7D%7B1%7D%3D%5Cpm11)
![\pm\frac{1}{1}=\pm1](https://tex.z-dn.net/?f=%5Cpm%5Cfrac%7B1%7D%7B1%7D%3D%5Cpm1)
![\pm\frac{11}{5}](https://tex.z-dn.net/?f=%5Cpm%5Cfrac%7B11%7D%7B5%7D)
![\pm\frac{1}{5}](https://tex.z-dn.net/?f=%5Cpm%5Cfrac%7B1%7D%7B5%7D)
The answer is: " 9a² + 7a " .
_________________________________
Note: (3a)² + 7a = (3a)*(3a) + 7a = 9a² + 7a .
_________________________________
14/18-9/18=5/18 it can't be simplified anymore